2020
DOI: 10.3390/foods9030268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extending Hard-Cheese Ripening: A Multiparameter Characterization of Parmigiano Reggiano Cheese Ripened up to 50 Months

Abstract: Extending ripening of hard cheeses well beyond the traditional ripening period is becoming increasingly popular, although little is known about the actual evolution of their characteristics. The present work aimed at investigating selected traits of Parmigiano Reggiano cheese ripened for 12, 18, 24, 30, 40 and 50 months. Two cheeses per each ripening period were sampled. Although moisture constantly decreased and was close to 25% in 50-month cheeses, with a parallel increase in cheese hardness, several biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 42 publications
4
46
2
1
Order By: Relevance
“…In general, L* values were in line [51] or lower [47,49] with those reported for Parmigiano Reggiano cheese ripened up to 50 months; by considering other PDO ripened Italian cheeses such as Montasio and Asiago cheeses, L* a* b* values were comparable, with the exception of b* values in the case of Asiago, which were lower [23,24,52].…”
Section: Color Characteristics Of the Cheesesupporting
confidence: 80%
See 1 more Smart Citation
“…In general, L* values were in line [51] or lower [47,49] with those reported for Parmigiano Reggiano cheese ripened up to 50 months; by considering other PDO ripened Italian cheeses such as Montasio and Asiago cheeses, L* a* b* values were comparable, with the exception of b* values in the case of Asiago, which were lower [23,24,52].…”
Section: Color Characteristics Of the Cheesesupporting
confidence: 80%
“…An increase in the lightness index L* during ripening time is an interesting finding for a long-ripened cheese type, as previous studies performed on various ripened cheeses reported a decrease of this parameter during ripening [ 23 , 24 , 37 , 46 , 47 ], that can be due to an increase in the hydration of proteins and a reduction of light scattering related to free water [ 48 ]. On the other hand, Sberveglieri et al [ 49 ] recently reported an increase in the L* index of Parmigiano Reggiano cheese during a 36-month period.…”
Section: Resultsmentioning
confidence: 99%
“…The fastest way to analyze these compounds is using SPME-GC/MS (Solid Phase Micro Extraction-Gas Chromatography/Mass Spectrometry). It is widely used among researchers for milk and dairy products [ 11 , 12 , 13 , 14 , 15 ] and other foods [ 16 , 17 , 18 ]. It is used also in the flavoromics approach [ 19 , 20 ], because it is capable of ppb detection level for a wide range of molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of casein fractions was evaluated by capillary zone electrophoresis (CZE) using a P/ACE TM MDQplus equipment (AB Sciex, Milan, Italy) and a hydrophilically coated capillary column DB-WAX126-7012 (50 cm length, 50 µm i.d., 0.05 µm coating, 100 × 800 µm slit opening) (Agilent Technologies, Milan, Italy). The analytical conditions were those described by D’Incecco et al [ 14 ]. Briefly, 1 g of grated cheese was added with 10 mL of sample buffer, kept at room temperature for 4 h, then diluted 1:5 with the same buffer and filtered with a 0.22 µm PVDF membrane filter (Merck, Milan, Italy) immediately before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Peak area ratios were calculated between selected casein breakdown fragments and the corresponding parent casein fractions. In particular, the ratios αs1-I-CN/αs1-CN and Σγ-CN/Σβ-CN described by D’Incecco et al [ 14 ] were considered as indicators of the primary proteolysis of αs1- and β-casein fractions, respectively.…”
Section: Methodsmentioning
confidence: 99%